Berhard Hring dan Program Teologi Moral Dasar - Mateus Mali (Jurnal Orientasi Baru, 2006)
Bernhard Hring is well known as a progressive moralist because he tries to progress moral theology as a science. Moral theology - before the Second Vatican Council - is so much controlled by Vatican so moral theology can not develop itself. According to Hring, moral theology, as a science, has to explore our faith: our relationship with God. To aim this goal, Hring stresses 3 points as locus theologicus of moral theology: Christ as Person, His redemption and our daily life. Hring believes that christian morality is never pure morality but depends on the relationship with Christ. So, this is why Hring categorizes christian morality as morality of discipleship: You do because You believe in Christ.